Endo/exo binding of alkyl and aryl diammonium ions by cyclopentanocucurbit[6]uril. Issue 9 (21st June 2017) - Qu, Yun-Xia; Lin, Rui-Lian; Zhang, Yun-Qian; Zhou, Kai-Zhi; Zhou, Qing-Di; Zhu, Qian-Jiang; Tao, Zhu; Ma, Pei-Hua; Liu, Jing-Xin; Wei, Gang
Abstract : Binding interactions of cyclopentanocucurbit[6]uril (CyP6 Q[6]) with a series of alkyl and aryl diammonium ions were investigated. CyP6 Q[6] exhibits endo and exo binding modes with the guests, which depends on the size and shape complementarity between the host and the guests. Abstract : The binding interactions of CyP6 Q[6] with a series of alkyl diammonium ( + H3 N(CH2 ) n NH3 +, n = 2, 4, 6, 8, 10, 12) and aryl diammonium ( p -phenylenediammonium and p -xylenediammonium) ions both in aqueous solution and in the solid state have been studied by 1 H NMR spectroscopy, X-ray crystallography, and isothermal titration calorimetry (ITC) techniques. 1 H NMR data indicate that all guests exhibit endo binding with CyP6 Q[6] except for the ethanediammonium ion, which bound exo to CyP6 Q[6]. p -Xylenediammonium ions show mixed behavior ( exo and endo binding with CyP6 Q[6]). X-ray crystallography clearly displays the extended and contorted conformations of the guests when bound within CyP6 Q[6]. The ITC study points out that the CyP6 Q[6] complex formations with all guests are mainly driven by enthalpy, which arises from the ion–dipole interactions and the hydrophobic effects.